Special Intellectual Property Protection for Traditional Cultural Expressions: Rectifying Broad Legal Approaches - Agustianto Agustianto; Hari Sutra Disemadi; Oda Ignatius Besar Hariyanto; Dame Afrina Sihombing (Nurani)
The legal protection of cultural diversity within the context of Traditional Cultural Expressions (TCEs) is not governed by specific legislation, which can significantly hinder the protection and validity of cultural expressions. Utilizing normative legal research methods, this study aims to conduct a comprehensive analysis of the urgency of establishing a specialized legal regime that recognizes and safeguards TCEs as a unique form of communal intellectual property. The analysis supported with a statutory approach indicates that there is a strong urgency to form this specialized legal regime, highlighting normative conflicts in existing regulations. The analysis also outlines how the formation of this regime can be accomplished by referring to a comprehensive normative framework and considering the unique elements that constitute TCEs. The research findings show that existing regulations have not been able to provide adequate protection for TCEs, especially in the context of the Industrial Revolution 4.0, which demands more comprehensive protection, particularly in the digital realm. Therefore, the establishment of this specialized legal regime becomes a crucial step in addressing new challenges in the era of Industrial Revolution 4.0.